2018
DOI: 10.1039/c7sc05016j
|View full text |Cite
|
Sign up to set email alerts
|

The impact ofO-glycan chemistry on the stability of intrinsically disordered proteins

Abstract: Protein glycosylation is a diverse post-translational modification that serves myriad biological functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Proline also follow the same pattern as glycine, however, its abundance may be due to the presence of pyrrolidine ring which contain imino group present in its side chain, which allows it to introduce kinks or turns in the protein structure. It is well known that high proline content is generally found in disordered proteins {Prates, 2018 #60}. Our results from this study lead us to propose that a spatial separation between sites of N-glycosites and protein disordered region sites potentially acts as a constraint to distinguish residue stretches that contribute to protein structure and function.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Proline also follow the same pattern as glycine, however, its abundance may be due to the presence of pyrrolidine ring which contain imino group present in its side chain, which allows it to introduce kinks or turns in the protein structure. It is well known that high proline content is generally found in disordered proteins {Prates, 2018 #60}. Our results from this study lead us to propose that a spatial separation between sites of N-glycosites and protein disordered region sites potentially acts as a constraint to distinguish residue stretches that contribute to protein structure and function.…”
Section: Discussionsupporting
confidence: 57%
“…In addition to phosphorylation, O-linked glycosylations have also been predicted to inhabit the disordered regions of proteins (Nishikawa et al, 2010). It is reported that the evolutionary selection favored the resistance to proteolysis by coevolution of protein sequence with the site of O-glycosylation (Prates et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of pyrrolidine ring-containing proline allows it to introduce kinks or turns in the protein structure and contributes to its propensity within interdomain linkers. It is well known that proline content is generally higher within disordered stretches 22 . Therefore, N-glycosite neighborhoods are uniquely placed in terms of their biochemical properties separating them from the hydrophobic ordered core and the disordered stretches of N-linked glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate steps in N-glycan biosynthesis act as checkpoints to ensure that only correctly folded proteins traffic along the ER-Golgi axis 24 . Thermodynamic and molecular dynamics studies show that glycans enhance the stability of the tertiary structure of proteins 22,25,26 . Keeping the above observations in mind, we asked whether the sites of N-glycan conjugation (N-glycosites) showed any bias in their locations vis-a-vis (dis)ordered regions of N-glycoproteins.…”
mentioning
confidence: 99%